Effects of CeO2 on microstructure and corrosion resistance of TiC-VC reinforced Fe-based laser cladding layers - 张辉 邹勇 邹增大 史传伟 (Journal of rare earths, 2014)
The effects of CeO2 on microstructure and corrosion resistance of TiC-VC reinforced Fe-based laser cladding layers were investigated. The results showed that carbides presented in cladding layers were TiVC2 and VC. A small quantity of CeC appeared with 2.0 wt.% CeO2 addition. The amount of lamellar pearlite increased while the amount of residual austenite decreased with increasing CeO2 addition. The corrosion resistance of cladding layers increased firstly and then decreased with the addition of CeO2 increasing. The EIS spectrum of the cladding layer without CeO2 was composed of an inductive arc at low frequency and a capacitive arc at high frequency. The cladding layer with 0.5 wt.% CeO2 addition showed the best corrosion resistance, and then the inductive arc at low frequency transformed into a capacitive arc.